INFLUENCE OF PROFITABILITY, SOLVENCY, COMPANY SIZE, AND AUDITOR'S OPINION ON AUDIT DELAY - Isnan Murdiansyah; Febianty Wulan Sari (Kajian Akuntansi, 2023)
There are many cases of companies that are late in reporting financial statements because an audit by an independent auditor takes quite a long time before being submitted to the OJK for publication. This study aims to determine the effect of profitability, solvency, company size, and auditor's opinion on audit delay in healthcare companies listed on the IDX from 2019 to 2021. This study uses purposive sampling; the population is healthcare companies listed on the Indonesia Stock Exchange, and the sample size is 54. This research applies data analysis, namely multiple linear regression analysis with a panel data regression model. Since this research uses the combined data of time series and cross-section, the analytical technique used in the analysis process to obtain more accurate results is multiple linear regressions with panel data. The data obtained is then processed using Microsoft Excel and SPSS version 26. The results show that the variables of profitability, solvency, firm size, and auditor's opinion have no significant effect on audit delay; those variables also have no simultaneous effect on audit delay. Keywords: Profitability, Solvency, Company Size, Auditor Opinion,  Audit Delay.